Women’s experiences and decision making about physical activity during pregnancy in Kaski district - Poudel, Sharmila; Gurung, Rajmi; Shrestha, Shreejana; KC, Deepti (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Physical activity during pregnancy affects multiple aspects of a woman’s life. Attitudes, values, experiences, and socio-cultural contexts play an important role in participation in physical activity. This study aimed to explore pregnant women lived experiences and perceptions of physical activity.Methods: A qualitative phenomenological study was conducted among women attending obstetrics outpatient department of Gandaki Medical College Teaching Hospital and Research Centre. Purposive sampling was used to recruit participants meeting inclusion criteria. The researchers performed semi-structured interviews, audio recorded them, transcribed the verbatim, and used thematic analysis. This approach focused on capturing the essence of participants lived experiences while organizing data into meaningful patterns.Results: Three major experiential themes emerged. 1) Perceptions of Pregnancy and Physical Activity: Women recognized the benefits of exercise but had limited knowledge of safe types, intensity, and frequency, often equating physical activity with household chores. 2) Experiences and Influences on Physical Activity: Participation was influenced by perceived benefits, fear of harming the foetus, fatigue, and social or cultural restrictions. Support from spouses, family, peers, and community resources facilitated engagement. 3) Experiences with Healthcare Providers and Recommendations: Guidance from healthcare professionals was often inadequate, leaving women uncertain about safe practices. Participants suggested structured counselling, practical demonstrations, family support, and accessible community programs to promote safe physical activity during pregnancy.Conclusions: Pregnant women recognize the benefits of physical activity but possess limited understanding of appropriate exercises, frequency, and safety. Interventions promoting physical activity should address informational gaps and take sociocultural circumstances into account.